The effects of metapopulation structure on indirect interactions in host-parasitoid assemblages. - Bonsall, M; Hassell, M (2000)
The interaction between two species that do not compete for resources but share a common natural enemy is known as apparent competition. In the absence of other limiting factors, such three-species interactions are impermanent, with one species being excluded from the assemblage by the natural enemy. Here, the effects of metapopulation structure are explored in a system of two hosts that experience apparent competition through a shared parasitoid. A coupled-map lattice model is developed and used to explore species coexistence and patterns of patch occupancy at the metapopulation scale. Linking local and regional dynamics favours coexistence by uncoupling the dynamics of the three species in space. Coexistence is promoted by the inferior species being either a fugitive or a sedentary species. The occurrence of these two mutually exclusive mechanisms of coexistence is influenced by the relative dispersal of the inferior apparent competitor.